PENINGKATAN KETERAMPILAN BERPIKIR KRITIS SISWA DENGAN MENERAPKAN MODEL CIRC PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS V MI - Nurhasanah, Nina Zakia; Heryati, Yeti; Mahmud, Muhammad Rifqi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study was conducted at Madrasah Ibtidaiyah Negeri 2 Kota Bandung due to the low level of students’ critical thinking skills in Indonesian language learning. Based on the End-of-Semester Summative Assessment, only 61.11% of fifth-grade students met the Learning Objectives Mastery Criteria (KKTP), while 38.89% had not yet reached the standard. This indicates the need for a more effective learning strategy. The purpose of this study was to examine the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) model in improving students’ critical thinking skills. The research focused on students’ initial abilities, model implementation, changes in learning outcomes, and comparisons between the experimental and control classes. The study employed a quasi-experimental method with a Nonequivalent Control Group Design. The experimental class was taught using the CIRC model, while the control class used Direct Instruction. Data were collected through observation, tests, and documentation. The pretest results showed similar initial abilities, with average scores of 31 in the experimental class and 33 in the control class. The Mann-Whitney test showed a significance value of 0.583, indicating no significant difference. After the intervention, the experimental class’s posttest average increased to 86, while the control class reached 59. The independent sample t-test showed a significance value of 0.0001, proving a significant difference. The experimental class achieved an N-Gain of 0.81 (high category), higher than the control class’s 0.40 (moderate category). These findings confirm that the CIRC model effectively improves students’ critical thinking skills.